Methods and Tools for Drought Analysis and Management - Rossi, Giuseppe; Vega, Teodoro; Bonaccorso, Brunella (Water Science and Technology Library, 2007)
Implementation of effective drought management policies requires both advanced technologies and appropriate methods. Monitoring and forecasting systems, practical tools for risk assessment, as well as simple and objective criteria to select and implement appropriate drought mitigation measures are key elements for a successful drought management strategy. These key issues have been tackled by universities and public agencies involved in the EU projects Sedemed and Sedemed II (Programme Interreg IIIB MEDOCC), aimed at the definition of an integrated network for real time monitoring of drought, the development of common methodologies for drought analysis and forecasting, as well as the definition of proper mitigation strategies for the Mediterranean countries. The book presents the main outcomes of such projects with a special focus on: drought monitoring and forecasting techniques at different spatial scales; new or modified agrometeorological indices and remote sensing technique for drought identification and characterization; tools to improve surface water resources management under drought conditions; methods and tools for groundwater resources monitoring and management, based on hydrogeological and hydrodynamics characteristics of aquifers; general criteria to select and implement mitigation strategies to prevent or minimize drought impacts.